Tasos Leivaditis' Triptych : Battle at the Edge of the Night, This Star Is for All of Us, The Wind at the Crossroads of the World. - Trakakis, N. N. (Anthem Impact., 2022)
Tasos Leivaditis made his stunning literary debut in 1952-53 with three poetry books, counteracting the violence and oppression of his times with the values of eros and solidarity, freedom and justice.